ADMINISTRATIVE MANAGEMENT OF CORRESPONDENCE AT SMP NEGERI 3 PAGUYAMAN PANTAI - asri sadikun (Jurnal Ilmu Manajemen dan Bisnis, 2022)
ABSTRACT This study aims to determine the administrative management of correspondence at the SMP N 3 PaguyamanPantai. The method in this study uses descriptive qualitative methods with data collection techniques of observation, in-depth interviews and documentation. The results of the study explained that the handling of incoming letters carried out at SMP Negeri 3 PaguyamanPantai was quite good and correct in accordance with existing theory. In handling incoming mail manually includes receiving letters, recording letters, directing letters, sorting letters and storing letters. Handling outgoing mail electronically is not entirely done electronically, but is done simultaneously manually. In handling outgoing letters, letter dictation is carried out, letter drafting, letter draft approval, letter typing, letter editing, letter signing, letter numbering, letter storage and letter delivery.